HEALTH AND LOCAL CULTURE: AN OVERVIEW OF RELIGIOUS LAW AND ITS RELEVANCE IN THE MODERN ERA - Normala Dewi, Nilam Nastiti; Mubiina Munief Fajri, Muh Fathan; Rifa’i, Moh; Fahmi Sanjani, M Aqil; Jaannah, Ulfa Qomariatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
In the context of Indonesian society, health practices are often influenced by local culture, which is rich in traditions and values of wisdom. However, religious legal values also have a significant role in shaping people's views on health. The relationship between these two aspects raises various deep questions. How exactly can local culture-based health practices harmonize with religious legal values? Can the two go hand in hand, or is there a potential for conflict? The modern era brings new challenges in integrating local traditions with the ever-growing development of health science. This challenge also includes how the principles of religious law remain relevant in maintaining a balance between preserving local culture and the need for adaptation to modern progress. Amid this rapid change, exploring how religious law can support traditional health practices without ignoring modern scientific values is essential. This research uses qualitative methods with a literature study approach (library research). The aim is to analyze the relationship between health, local culture and Islamic teachings, assess the role of local culture in an Islamic perspective, examine the relevance of Islamic teachings in a modern context, and formulate practical steps by sharia to maintain health and respect local culture. The research results show that the synergy between Islamic teachings, local culture and health can create a healthy, harmonious society that adheres to religious values, even amidst the challenges of modern progress.